Aerobic exercise acutely increases EEG gamma power in the motor/sensorimotor areas during walking in people with Parkinson’s disease - Orcioli-Silva, Diego [UNESP]; Vitório, Rodrigo; Beretta, Victor Spiandor [UNESP]; Souza Oliveira, Anderson; Conceição, Núbia Ribeiro da; Nóbrega-Sousa, Priscila; Santos, Paulo Cezar Rocha Dos; Gobbi, Lilian Teresa Bucken [UNESP]; Barela, José Angelo [UNESP] (Elsevier, 2025)
OBJECTIVE: This study investigated the effects of acute aerobic exercise on gait function and cortical activity during single and dual-task walking in people with Parkinson's disease (PwPD). METHODS: Thirty PwPD were randomly assigned to the Experimental (EG) and Control Group (CG). Both groups completed a single 40-minute session of cycling. Exercise intensity was maintained at 65-70% of the maximum heart rate for EG and within 5% of the resting heart rate for CG. Participants performed five walking trials under each condition before and after exercise. EEG and accelerometers measured cortical activity and gait parameters. RESULTS: In the post- vs. pre-exercise, the EG increased gamma power in the C and CP channels during single and dual-task walking. Increased step length during dual-task condition was positively associated with increased gamma power at the C and CP channels. CONCLUSION: Acute exercise enhances movement control and sensorimotor integration during walking, evidenced by increased gamma power. Changes in gamma power in the motor/sensorimotor areas may improve step length during dual-task walking. SIGNIFICANCE: This study underscores the potential of aerobic exercise to increase the involvement of motor and sensorimotor cortical regions, highlighting the relevance of aerobic exercise in the neurorehabilitation and gait functions in PwPD.